Preliminary study on the tick population of Benin wildlife at the moment of its invasion by the Rhipicephalus microplus tick (Canestrini, 1888) - Adinci, Kossi Justin; AKPO, YAO; ADOLIGBE, CAMUS (My University, 2018)
Background and Aim: Rhipicephalus microplus (Rm) is one of the most problematic livestock tick species in the world. Its rapid propagation and resistance to acaricides make it control difficult in the sub-region and Benin particularly. The aim of this work was to check its presence in wildlife and to confirm the possible role of reservoir wildlife may play in the propagation of the parasite. This will help to design more efficient control strategy. Materials and Methods: This study was conducted from February to March 2017 in the National Parks of Benin (Pendjari and W Park) and wildfowl’s assembly and selling point in Benin. Ticks were manually picked with forceps from each animal after slaughtering by hunters then stored in 70° ethanol. Collected ticks were counted and identified in the laboratory using the identification key as described by Walker. Results: Overall, seven species of ticks (Amblyomma variegatum, Boophilus decoloratus, Rm, Boophilus spp., Hyalomma spp., Rhipicephalus sanguineus, Rhipicephalus spp.) were identified on nine wild animal species sampled (Cane rat, wildcat, Hare, Doe, Cricetoma, Buffalo, Buffon Cobe, and Bushbuck and Warthog). The average number of ticks varies from 3 to 6 between animal species, 3 to 7 between localities visited, and 2 to 5 between tick species. However, these differences are statistically significant only for localities. Considering tick species and animal species, the parasite load of Rm and Rhipicephalus spp. is higher; the buffalo being more infested. The analysis of deviance reveals that the abundance of ticks observed depends only on the observed localities (p>0.05). However, the interactions between animal species and localities on the one hand and between animal and tick species on the other hand, although not significant, have influenced the abundance of ticks as they reduce the residual deviance after their inclusion in the model. Conclusion: This study reported the presence of Rm in wildlife of Benin and confirmed its role in the maintenance and spread of the parasites. It is, therefore, an important risk factor that we must not neglect in the epidemiological surveillance and ticks control strategies in the West African sub-region and particularly in Benin. Keywords: Benin, Rhipicephalus microplus, ticks, wild animals.
Keywords: Benin; Rhipicephalus microplus; ticks; wild animal